2020
DOI: 10.1177/1535370220929287
|View full text |Cite
|
Sign up to set email alerts
|

NAD metabolism in aging and cancer

Abstract: NAD+ and its derivatives NADH, NADP+, and NADPH are essential cofactors in redox reactions and electron transport pathways. NAD serves also as substrate for an extensive series of regulatory enzymes including cyclic ADP-ribose hydrolases, mono(ADP-ribosyl)transferases, poly(ADP-ribose) polymerases, and sirtuin deacetylases which are O-acetyl-ADP-ribosyltransferases. As a result of the numerous and diverse enzymes that utilize NAD as well as depend on its synthesis and concentration, significant interest has de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 259 publications
(331 reference statements)
0
13
0
Order By: Relevance
“… 40 Our results showed that NAD+/NADH ratio was decreased in 18 M BMSCs. Since abnormal NAD levels may lead to a variety of diseases, including aging process and inflammatory diseases, 41 , 42 , 43 we hypothesized that aging can weaken the mitochondrial function of BMSCs by reducing the proportion of NAD+. In addition, in eukaryotes, electrons received during glycolysis, oxidative phosphorylation, and oxidation of fatty acids are transferred to the electron transfer chain to form ATP.…”
Section: Discussionmentioning
confidence: 99%
“… 40 Our results showed that NAD+/NADH ratio was decreased in 18 M BMSCs. Since abnormal NAD levels may lead to a variety of diseases, including aging process and inflammatory diseases, 41 , 42 , 43 we hypothesized that aging can weaken the mitochondrial function of BMSCs by reducing the proportion of NAD+. In addition, in eukaryotes, electrons received during glycolysis, oxidative phosphorylation, and oxidation of fatty acids are transferred to the electron transfer chain to form ATP.…”
Section: Discussionmentioning
confidence: 99%
“…These conditions are now seen significantly more often among cancer survivors, years after their cancer diagnosis and treatment. NAD + biosynthetic and metabolic processes are mechanistically involved in aging, cancer, and many age-associated comorbidities [ 184 ] , and therapies aimed at raising intracellular NAD + may remedy accelerated aging and age-associated diseases in cancer survivors. In fact, there are several ongoing clinical studies examining supplementation with NAD + precursors as a therapeutic option for age-related diseases [ Table 1 ].…”
Section: Aging-related Diseases In Cancer Survivorsmentioning
confidence: 99%
“…10,11 As a central cofactor, nicotinamide adenine dinucleotide (NAD + ) could modulate metabolic homeostasis and be a rate-limiting substrate for sirtuin deacetylases. 12 Multiple lines of evidence indicate that NAD + levels perform a crucial role in nuclear-mitochondrial interaction in aging. 6 In addition, the NAD + precursor NMN has been proven to enhance NAD + biosynthesis and ameliorate multiple pathologies in mouse disease models.…”
Section: Nicotinamide Mononucleotide Ameliorates Acute Lung Injury By...mentioning
confidence: 99%